Distribui Spasial Permukiman Kumuh Di Kecamatan Palu Selatan Kota Palu - Rusman, Afandi; Saputra, Iwan Alim (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2024)
This study aims to find out how the spatial distribution of slum-prone areas in South Palu District. This type of research uses Quantitative, the type of research data used is Primary and Secondary Data. The sample in this study uses BIG Image. The method in this study uses a spatial approach. Based on the results of research on the Spatial Distribution of Slums in South Palu District, researchers can draw conclusions. The distribution of slums in the southern part of Palu City is categorized into medium to low slum levels. north and south, namely blocks 2, 3, 4, and 7, fall into the moderate slum category in parts of the northern slum area, southern Birobuli and the Petobo area, namely blocks 1, 5, 6 and 10, while those that fall into the low slum category are in the North Tatura and South Birobuli.